Physical activity, intake of iron and folic acid with the risk of preeclampsia - Dwi Apriyanti; Uki Retno Budihastuti; Kusnandar Kusnandar (AcTion: Aceh Nutrition Journal, 2023)
Preeclampsia (PE) is a health problem that often occurs during pregnancy. Pregnant women with preeclampsia are at risk for premature delivery, babies born with LBW, and increased maternal and infant mortality. This study aimed to measure the effect of physical activity and iron and folic acid intake on the risk of preeclampsia in pregnant women. A cross-sectional study was conducted in the Tangerang Regency in July 2022. 130 pregnant women aged ≥ 20 weeks were obtained using multistage sampling. Data were collected using the SQ-FFQ (the Semi-quantitative Food Frequency) Questionnaire (SQ-FFQ) and Physical Activity using a validated PAL (physical activity level) questionnaire. Data analysis was performed using Spearman’s rank and Multiple Linear Regression tests. Results: There was an association between iron and folic acid micronutrient intake and preeclampsia incidence in pregnant women (p<0,05). Furthermore, simultaneous physical activity and iron and folic acid intake increased the risk of preeclampsia in pregnant women (p<0,05) by 10,7%. In conclusion, lack of physical activity and consumption of nutritious foods, especially those containing iron and folic acid, can increase the risk of preeclampsia during pregnancy.